MODIFIED UTAUT2 APPROACH TO PREDICT IN-GAME PURCHASE BEHAVIOR: EVIDENCE FROM MOBILE LEGENDS PLAYERS - Melyanto, Melyanto; Tandra, Vinsen; Yuricha, Yuricha (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2025)
This study aims to examine the factors influencing in-game purchasing behavior among Mobile Legends players by utilizing a modified UTAUT2 framework. Specifically, it explores the roles of hedonic motivation, price value, habit, and behavioral intention. A quantitative approach was employed, using purposive sampling to collect data from 96 respondents aged 16–25 in West Kalimantan. The data were analyzed through regression analysis and hypothesis testing. The findings indicate that behavioral intention is the strongest predictor of actual use behavior. Moreover, hedonic motivation and habit significantly affect behavioral intention, while price value and habit exhibit partial mediation through intention. Gender was also found to moderate several of these relationships. These results contribute to a deeper understanding of digital consumer behavior among Gen Z gamers, emphasizing the importance of emotional satisfaction and habitual engagement. The study offers practical insights for developing gender-sensitive marketing strategies within virtual gaming environments.